Antibiotic Resistance of the Campylobacter Isolates According to Their Species in Different Samples of Broiler Chicken in Many Regions - Elma Hrustemović; Faruk Čaklovica; Jasmina Đeđibegović; Muhamed Smajlović; K Čaklovica; Enida Članjak Kudra (Indonesian Center for Animal Research and Development, 2022)
Campylobacter jejuni and C. coli are contaminants of broiler skin, and in unauthorized numbers cause campylobacteriosis in consumers where symptoms range from gastrointestinal to life-threatening. The number of chicken bacteria and their genetic diversity depend on the growing conditions, and the presence of antibiotic resistance genes is the result of irrational use of antibiotics. The purpose of this paper is to point out the importance of reducing the contamination of Campylobacter spp. in broiler production as well as the importance of the rational use of antibiotics in the production of broilers with a contribution to the prevention of the spread of campylobacteriosis and antibiotic resistance. The incidence of campylobacteriosis can be prevented by the concept of Hazard Analysis Critical Control Point (HACCP) in broiler production and the use of probiotics as biological preservatives in broiler meat. The spread of antibiotic resistance genes can be reduced by prohibition of antibiotic use for prophylaxis and only permitted for medication.